PENGEMBANGAN BAHAN AJAR BERBASIS PROJECT BASED LEARNING PADA MATERI TEORI ASAM BASA, pH LARUTAN DAN TITRASI ASAM BASA DI KELAS XI IPA - Muhammad Evan; Andi Suharman; M Hadeli L; Made Sukaryawan; Sanjaya Sanjaya (Chemistry Education Study Program Sriwijaya University, 2023)
This research is a development research that produces teaching materials based on project-based learning (PjBL) on acid-base theory, pH solutions and acid-base titrations for class XI IPA. The development model used is the Four Steps Teaching Material Development (4S-TMD). Data collection was carried out by interviews, questionnaires, validation and tests. The results of the validation of teaching materials developed from the three aspects material, pedagogic, and design, obtained an average validity score of 0.93 in the high category and declared valid. The practicality test results that have been carried out and analyzed obtain a practicality value of 0.80 where the score is categorized as high so that it is considered practical. The results of the effectiveness test of teaching materials by looking at student learning outcomes based on pretest and posttest scores are then calculated for the N-Gain. The N-Gain score obtained was 0.72 where the score was in the high category range and was declared effective. Thus the project-based learning-based teaching materials that have been developed are stated to be valid, practical and effective so that they are suitable for use in the chemistry learning process for acid-base theory , pH solutions and acid-base titrations in class XI IPA.